Effect of arbuscular mychorrhizal fungi inoculation on growth and Cu uptake and toxicity of Demodium cinereum (Kunth) D.C - Adiova, Joden M. (Philippine Journal of Science, 2013)
The effect of arbuscular mycorrhizal fungi (AMF) inoculation on copper (Cu) uptake and toxicity of Desmodium cinereum (Kunth) D.C. was studied. This legume produces large amount of biomass that can serve as buffer in areas with high concentration of Cu. Pre-germinated seeds of D. cinereum inoculated and non-inoculated with AMF were grown in sand-soil mixture treated with increasing Cu concentration (0, 400, 800, 1200, 1600ppm Cu). Increasing Cu concentration gave a corresponding reduction on height, diameter, leaf area, and biomass of the plants. Root growth and nodule formation at 1200 and 1600ppm Cu level were inhibited (p<0.05 and p<0.01, respectively). Mycorrhizal inoculation increased plant height, biomass, and stem diameter at lower Cu level. Inoculation enhanced nodulation and also improved phosphorus concentration in the leaves, stem and roots at 0 and 400ppm Cu level. Increasing Cu concentration resulted to a greater Cu accumulation in the roots while Cu concentration on stem and leaves remained at a normal level. Inoculation with AMF increased Cu uptake of roots and stem at 800, 1200, and 1600ppm Cu levels. The ability of mycorrhizal fungi to improve Cu uptake, increase plant growth, increase phosphorus uptake, and promote growth of other beneficial microorganisms such as nitrogen fixing bacteria (as exemplified by the nodulation in the roots) for D. cinereum, make it an ideal tool for phytoremediation of Cu contaminated sites.